Designing and implementing smart glass technology for emergency medical services: a sociotechnical perspective. Issue 4 (30th December 2022) - Zhang, Zhan; Ramiya Ramesh Babu, Noubrab Ashika; Adelgais, Kathleen; Ozkaynak, Mustafa
Abstract: Objective: This study aims to investigate key considerations and critical factors that influence the implementation and adoption of smart glasses in fast-paced medical settings such as emergency medical services (EMS). Materials and Methods: We employed a sociotechnical theoretical framework and conducted a set of participatory design workshops with 15 EMS providers to elicit their opinions and concerns about using smart glasses in real practice. Results: Smart glasses were recognized as a useful tool to improve EMS workflow given their hands-free nature and capability of processing and capturing various patient data. Out of the 8 dimensions of the sociotechnical model, we found that hardware and software, human-computer interface, workflow, and external rules and regulations were cited as the major factors that could influence the adoption of this novel technology. EMS participants highlighted several key requirements for the successful implementation of smart glasses in the EMS context, such as durable devices, easy-to-use and minimal interface design, seamless integration with existing systems and workflow, and secure data management. Discussion: Applications of the sociotechnical model allowed us to identify a range of factors, including not only technical aspects, but also social, organizational, and human factors, that impact the implementation and uptake of smart glasses in EMS. Our work informs design implications for smart glass applications to fulfill EMS providers' needs. Conclusion: The successful implementation of smart glasses in EMS and other dynamic healthcare settings needs careful consideration of sociotechnical issues and close collaboration between different stakeholders. Lay Summary: Smart glass technology has been tested in various healthcare settings over the past decade. However, limited research has investigated the potential application of this technology in fast-paced, hands-busy medical settings, such as emergency medical services (EMS). Our study aims to address this critical research gap by investigating key considerations and critical factors that influence the implementation and adoption of smart glasses in time-critical medical settings through the lens of a sociotechnical perspective. We conducted a set of design workshops with EMS providers to understand what factors can facilitate or hinder the uptake of smart glasses. Our results highlighted several key user concerns and considerations that must be thoroughly addressed, such as the requirement for durable and weather-proof devices and long-lasting batteries, easy-to-use user interface, seamless workflow integration, and regulation-compliant data management. The results of this study can inform design, implementation, and evaluation of future smart glass applications to better support emergency patient care. We call for closer collaboration among different stakeholders, including device manufacturers, system designers, researchers, policymakers, and medical practitioners.